THEORETICAL SUBSTANTIATION OF THE EFFICIENCY OF MACHINES FOR EARTH WORKS BASED ON THEIR TECHNICAL PARAMETERS - Remarchuk, М.; Kebko, O.; Halytsky, O. (Municipal economy of cities. Series: «Economy science», 2022)
The characteristic features of modern MZRs are that they are divided into cyclic and continuous machines, which depends on their productivity and power of internal combustion engines, and the design of their working equipment affects the process of specific application of MZRs for the construction of appropriate earthworks with different labor intensity. When using MZR, the main question arises about the effectiveness of their functioning from the point of view of knowing the actual state, the amount of fuel consumption required to perform a given volume of work and inefficient fuel losses. The purpose of the article is to determine the real state for known MZR based on the use of reference parameters and to ensure the given state at the design stage of such machines based on the application of system analysis with the establishment of numerical indicators that are characterized by objectivity, ambiguity and accuracy of their determination. The conducted studies are based on the application of system analysis when considering MZR using their reference technical and economic parameters, as a complex system with structural elements functionally interconnected and capable of transmitting hydraulic and mechanical energy. Moreover, MZR is studied as a system that is suitable for converting input power into useful work at the output and, on this basis, is able to determine its internal state due to the overall efficiency and the amount of specific fuel consumption. Based on the results of the research, it was found that the most effective MZR are machines with a continuous working process and they are characterized by high values of the total efficiency of the machine at the level of (8 to 14)%, and gradually the total efficiency decreases to several tenths of a percent for machines of cyclic action. Research has established that in each of the ten MZR groups there is a machine that has the highest total efficiency, and the value of specific fuel consumption per unit of productivity for it is the smallest, and such a machine is classified as exemplary. Other MZR from this group with a low value of total efficiency and higher specific fuel consumption are classified as ordinary cars. According to the conducted studies, it is possible to ensure the selection of the best MZR to create a squad of machines from them, directed to perform a specific volume of work with minimal fuel loss. The internal state of MZR by the value of the total efficiency can be diagnosed at the stage of completion of production, as well as during operation due to the measurement of input and output parameters based on the use of modern means for recording these parameters.